1977
DOI: 10.1093/nar/4.6.1933
|View full text |Cite
|
Sign up to set email alerts
|

Poly-2′-deoxy-2′-fluoro-cytidylic acid: enzymatic synthesis, spectroscopic characterization and interaction with poly-inosinic acid

Abstract: The polymerization of 2'deoxy-2'-fluoro-cytidine-diphosphate (dCflDP) by polynucleotide phosphorylase is barely detectable in the presence of Mg++ under usual experimental conditions for polymerization of nucleoside diphosphates. High concentrations of enzyme have to be used to accomplish the synthesis. Mn++ is a better activator than Mg++ for the reaction. cCflDP inhibits the polymerization of CDP and has a Km=8.8X10-3M, six times higher than CDP.- The polymer, poly (dCfl), ressembles in many respects poly(C)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0
1

Year Published

1978
1978
2008
2008

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(19 citation statements)
references
References 25 publications
3
15
0
1
Order By: Relevance
“…The same increase in Na + had only a marginal, if any, effect on the p~ values of the DNA polymers. Our data were in reasonable agreement with those published by Guschlbauer and his collaborators for poly[r(C)], poly[r(A)], and poly[d(C)] (22,54). Moreover, poly[d(C)] had a pKa for the coil-helix transition that was the farthest from its monomerpKa, while poly[d(A)] was the only polymer whose p~ was essentially identical with that of its monomer.…”
Section: Effects Of Salt Concentration and Analysis Of Titration Datasupporting
confidence: 93%
See 2 more Smart Citations
“…The same increase in Na + had only a marginal, if any, effect on the p~ values of the DNA polymers. Our data were in reasonable agreement with those published by Guschlbauer and his collaborators for poly[r(C)], poly[r(A)], and poly[d(C)] (22,54). Moreover, poly[d(C)] had a pKa for the coil-helix transition that was the farthest from its monomerpKa, while poly[d(A)] was the only polymer whose p~ was essentially identical with that of its monomer.…”
Section: Effects Of Salt Concentration and Analysis Of Titration Datasupporting
confidence: 93%
“…Others have shown that protonation of poly[r(C)] increases as the pH is reduced to 3 (15), causing denaturation of the acid self-complex to form a fully protonated single-strand (15,23). We found, in agreement with previous work ( 15,22), that the fully protonated polymer was hyperchromic and had a much reduced long wavelength CD band, compared with the duplex form ( Figure 7).…”
Section: Poly[r(c)]supporting
confidence: 91%
See 1 more Smart Citation
“…C2modifications are known to affect the sugar puckering of nucleic acids [33,34]. The introduction of fluorine, the most electronegative element, leads to an almost pure C3 -endo conformation [36,37]. Heteroatom modifications like 2amino-groups favour a C2 -endo pucker, which is one of the main determinants of the "DNA-like" B-helix.…”
Section: Discussionmentioning
confidence: 99%
“…..... --.,... drogen bonding in some instances (87) (Figure 4-11a). However, O2, methylation (238)(239)(240) or replacement of O2, by chlorine (241), fluorine (242)(243)(244), or the azido group (245) does not markedly reduce the conformational stability of synthetic RNAs and therefore the 02,-H···04, hydrogen bond cannot be a crucial, structure-stabilizing factor. More recent NMR data suggest a water-mediated hydrogen-bonded bridge between 02,H and 3' -phosphate which could well account for at least part of the conformation rigidity of RNAs (246,247) (Figure 4-11b).…”
Section: Factors Affecting Furanose Puckering Modesmentioning
confidence: 99%